(untitled) (Fiep Bulletin - online, 2013)
The methodologies emerging of physical education school advocate that the contents to be discussed in class should make mention of knowledge historically produced in the fields of culture of body movement. However, the gímnics modalities remain relegated to the background, this fact can be caused by several factors, of which it is the lack of knowledge of gímnics content, or the terms and expressed their goals for physical education school. Among the possibilities for intervention, you can highlight the practice of Acrobatics Gymnastic, an arrangement that provides the development of strength, balance and confidence between the subjects practitioners, enabling work in schools explore the issue of diversity of knowledge brought by the students. The purpose of this study is to propose the application of acrobatics gymnastics within a social-constructivist perspective as a means of intervention of physical education classes in school. Characterized as descriptive, the sample consisted of 35 adolescents of both sexes, aged between 13 and 14 years of a School of Maringá-Pr. The data were obtained through application of pre and post intervention questionnaire. As results after the analysis found that 100% of students had never experienced the acrobatics gymnastics within the school environment, 71.5% of them did not have knowledge about this type of gímnic modalitie, noting that after the intervention 85.8% of students have formed an idea about the acrobatics gymnastics, 100% of adolescents supported the methodology used to produce the classes and 97.1% of the sample approved the acrobatics Lecturas: Educación Física y Deportes. A GACRO deveria ser trabalhada na Educação Física Escolar? Sim A GACRO deveria ser trabalhada na Educação Física Escolar? Não gymnastics as a means of intervention during school physical education school. It follows that, the acrobatics gymnastics based on social-constructivist theory, can break the deal purely technical, providing an overall development of cognitive functions, motor, affective and social allowances to students in the age group corresponding to adolescence.